2012
DOI: 10.1002/ece3.283
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial lineages in Notochthamalus scabrosus as indicators of coastal recruitment and interactions

Abstract: A significant genetic cline has previously been identified along the Chilean coast in the barnacle Notochthamalus scabrosus. Samples from the previous study, spanning 800 km, were not able to show whether the southern lineage ultimately goes to fixation at higher latitudes. In addition to expanding the geographic sampling of this species, locations that were sampled approximately four to five generations ago were resampled for this study, enabling a temporal comparison of the location and strength of the obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 54 publications
(86 reference statements)
0
20
0
Order By: Relevance
“…), or even change considerably from year to year (Laughlin et al. ), suggesting the importance of local habitat and mechanisms associated with larval recruitment for maintaining the biodiversity at a site.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…), or even change considerably from year to year (Laughlin et al. ), suggesting the importance of local habitat and mechanisms associated with larval recruitment for maintaining the biodiversity at a site.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of DNA from these tissues proceeded as in Laughlin et al. (). These samples were used for sequencing or haplogroup identification of mitochondrial COI and genotyping of 130 anonymous nuclear single nucleotide polymorphisms (SNP).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Well-known phylogeographic breaks in the Pacific are located at Point Conception (34.5° N) in California [27], 30–32° S in northern [28] and 42° S in southern Chile [29]. While studies performed in Chile have identified species limited by the break at 30–32° S [30,31], other species did not align with these biogeographic breaks [32,31]. …”
Section: Introductionmentioning
confidence: 99%